Patient and Clinician Perspectives on the use of Remote Patient Monitoring in Peritoneal Dialysis. (March 2022) - Talbot, Benjamin; Farnbach, Sara; Tong, Allison; Chadban, Steve; Sen, Shaundeep; Garvey, Vincent; Gallagher, Martin; Knight, John
Background: Numerous factors influence patient recruitment to, and retention on, peritoneal dialysis (PD), but a major challenge is a perceived "inaccessibility" to treating clinicians. It has been suggested that remote patient monitoring (RPM) could be a means of improving such oversight and, thereby, uptake of PD. Objective: To describe patient and clinician perspectives toward RPM and the use of applications (Apps) suitable for mobiles, tablets, or computers to support the provision of PD care. Design: Qualitative design using semi-structured interviews. Setting: All patient participants perform PD treatment at home under the oversight of an urban PD unit in Sydney, Australia. Patient and clinician interviews were conducted within the PD unit. Participants: 14 participants (5 clinicians [2 nephrologists, 3 PD nurses] and 9 patients treated with PD). Methods: Semi-structured interviews were conducted using interview guides tailored for clinician and patient participants. Transcripts were coded and analyzed by a single researcher using thematic analysis. Results: Six themes were identified: perceived benefits of RPM implementation (offering convenience and efficiency, patient assurance through increased surveillance, more complete data and monitoring adherence), uncertainty regarding data governance (protection of personal data, data reliability), reduced patient engagement (transfer of responsibility leading to complacency), changing patient-clinician relationships (reduced patient-initiated communication, the need to maintain patient independence), increased patient and clinician burden (inadequate technological literacy, overmanagement leading to frequent treatment changes), and clinician preference influencing patient behavior. Limitations: The interviews were conducted in English only and with participants from a single urban dialysis unit, which may limit generalizability. Conclusions: For patients and clinicians, advantages from the use of RPM in PD may include increased patient confidence and assurance, improved treatment oversight, more complete data capture, and overcoming barriers to data documentation. Careful patient selection and patient and clinician education may help to optimize the benefits of RPM, maintain patient independence, and reduce the risks of patient disengagement. The use of an App may support RPM; however, participants expressed concerns about increasing the burden on some patients through the use of unfamiliar technology. Human Research Ethics Committee Approval Number: CH62/6/2019-028